Diagnostic Accuracy of Clinical Tests in Knee Joint Injuries: A Single Centered Experience - Imran Khan; Junaid Zeb; Qaiser Khan; Mohammad Imran; Nabhan Rashad; Muhammad Ayaz Khan (Gandhara University, 2021)
OBJECTIVES: The accuracy of clinical tests (Lachman, McMurray, Anterior Drawer) in the diagnosis of knee joint injuries in comparison to arthroscopy taken as gold standard. METHODOLOGY: This cross-sectional study was conducted at the Department of Orthopedic Surgery, Khyber Teaching Hospital, Peshawar for 3 years. Total of 48 patients were recruited in the study. Data was collected after ethical approval from the hospital ethical committee using consecutive non-probability sampling techniques. Written informed consent was obtained from the patients. Arthroscopy examination was taken as a gold standard. Data analysis was performed using statistical software SPSS 21 and MEDCALC online software for calculating sensitivity and specificities of the clinical tests. RESULTS: Mean age was 26.4+6.5 years. Lachman and Anterior Drawer tests were noted to have 91.67% and 66.67% sensitivity for anterior cruciate ligament while McMurray test was noted only 66.67% sensitive for both meniscal injuries. On the other hand, Lachman was 95.8% specific, McMurray was 77.78%, and Anterior Drawer was 79.2% specific. Regarding accuracy, Lachman was 93.7%, McMurray 70.8% and Anterior Drawer was 72.9% accurate. CONCLUSION: Among clinical examination and specific examination tests, Lachman has high sensitivity, specificity and accuracy followed by Anterior Drawer test and MacMurray for diagnosing anterior cruciate ligament and meniscal injuries of knee joint.